Partisipasi Masyarakat dalam Meningkatkan Mutu Pendidikan di Madrasah Ibtidaiyah Maroanging Kabupaten Bulukumba - Samsiah Samsiah; Misykat Malik Ibrahim; Musdalifah Musdalifah (El-Idare, 2018)
This research aims to analyze and examine the effect of leadership style of headmaster to teacher discipline at Madrasah Ibtidaiyah of Bulukumba Regency, South Sulawesi. This research is a quantitative research with the ex post facto method. Respondents in this study as much as 92 teachers, taken at random. The data collection techniques used is a questionnaire then analyzed by using regression analysis to examine the hypotheses. The results of this study indicate that the leadership style of headmaster influential positive and significant to teacher discipline with determinants coefficient of 0,305. So, teacher discipline 30,5% influenced by the leadership style of headmaster and 869,5% determined by another factor.